Application of Untargeted Volatilomics for Halal Authentication of Processed Meat Products - Luthfi Nursaudah; Vevi Maritha; Weka Shidha Bhagawan; Puri Ratra Kartini; Desi Kusumawati; Avip Kurniawan (Strada Journal of Pharmacy, 2025)
Food halalness is essential for Muslim communities, including in Indonesia, where the majority of the population is Muslim. Halal food not only means free from prohibited ingredients, such as pork and alcohol, but must also be processed in accordance with Islamic law. With the increasing consumption of processed products such as nuggets, concerns about the authenticity of raw materials have become an important issue. This research aims to determine and classify the volatile compound profile of beef and pork nuggets for halal authentication using a combination of GC-MS and chemometric methods. The analysis data were processed using a multivariate statistical approach in the form of Principal Component Analysis (PCA), Cluster Analysis (CA), and Partial Least Squares Discriminant Analysis (PLS-DA). The research method used was a laboratory experimental study with a volatilomics approach using a combination of GC-MS and chemometric methods. The results showed significant differences in the volatile compound profiles between the two types of nuggets (with pork samples containing 68 volatile compounds and beef samples containing only 45 compounds), which allowed separation and classification based on chemical composition. Further analysis identified specific volatile compounds that have the potential to serve as markers of halal status. The result of the research was volatile compound profiles of beef and pork nuggets were successfully determined using the GC-MS method, showing differences in composition.